Evaluation of fracture toughness of zirconia silica nano-fibres reinforced feldespathic ceramic - Ahila Singaravel Chidambara Nathan; Rajdeep Tah; Muthu Kumar Balasubramanium (Elsevier, 2018)
Background: Dental ceramics exhibit great optical properties and better esthetics due to their translucency. Concern with this material is its brittleness, which accounts for its failure. Feldspathic ceramic is the most widely used veneering ceramic. Aim and objectives: To evaluate and compare the fracture toughness of pressable feldspathic ceramics reinforced with zirconia silica nano-fibres with conventional pressable feldspathic ceramics. Materials and method: According to ISO 6872, a master die was prepared from which, Bar shaped samples were formed in acrylic resin with the specified dimensions of 4.0 mm in width ×1.2 mm thickness ×25.0 mm. The zirconia silica nano-fibres were prepared by sol gel electro-spinning followed by calcination then they were incorporated into feldspathic ceramic through ball milling process. The samples were prepared with addition of 0, 2.5, 5, 7.5 weight % nano-fibres. The fracture toughnes was evaluated using the indentation strength method. The values were statistically analysed using the one sample Kolmogorov-Smirnoff test, Kruskal Wallis test and pair wise group comparison was done using Mann Whitney test with Bonferroni correction. Results: The fracture toughness values for 2.5 wt% and 5 wt% groups were higher than control group, while the values for 7.5 wt% groups were lower compared to control group. Conclusion: The fracture toughness values of feldspathic ceramic samples reinforced with zirconia silica nanofibers by 2.5 and 5 wt% were statistically significant when compared to samples reinforced with 7.5 wt%.